Outcome of Orthotopic Neobladder after Radical Cystectomy (Bangladesh Journal of Urology, 2012)
Objective: To assess the results of patients underwent radical cystectomy and orthotopic neobladder reconstruction (ONR) after radical cystectomy for muscle invasive transitional cell carcinoma of urinary bladder. Patients And Methods: The medical records were retrospectively reviewed for 154 suitable consecutive patients undergoing radical cystectomy and orthotopic neobladder reconstruction between July 1998 and June 2007 in BSMMU Hospital and in a private medical institution at Dhaka, Bangladesh. The operating time, transfusion rates, complications, mortality rates, continence rates, potency rates, disease specific survival and overall survival were reviewed. Results: The median (range) follow-up was 48 (6113) months; all patients had a reconstruction with a Studer type of neobladder, Retrospective review was possible in 98 patients. Data of other patient were incomplete or inadequate for result of potency and continence review. Full continence was defined as being dry and with freedom from pads. Continence could be assessed in 98 patients after orthotopic neobladder reconstruction. 96 patient out of 98 (97.95%) were classified as being fully continent, and two (2.40%) patient who were fully incontinent. The daytime continence rate was 99% (97 patients) and the nocturnal continence rate was preserved in 90 patients (91.83%). Of the 98 patients, 93 patients could empty their bladder leaving a residual urine less than 100 ml with a mean flow rate 12.5 ml/ sec. Only five patients used (5.10%) intermittent self-catheterization (ISC). All of them had a very large neobladder, of 600 ml capacity or more. Of the 98 men with an orthotopic neobladder, 69 ( 70.40%) were potent before surgery (potency being defined as the ability to achieve and maintain an unaided erection sufficient for sexual intercourse). Of these 69 patients, 57 (82.60%) were potent and 12(17.39%) were impotent after surgery. The patient who developed erectile dysfunction after surgery was given sildenafil 50 to 100 mg two hours prior to sexual contact. Of the 154 patients with malignancy after a median (range) follow-up of 48 (6 113) months, 109 (70.77%) remained alive with no sign of disease recurrence. During this period of follow up 32 patients developed tumor recurrence died from disease progression confirms the disease specific mortality was 20.77%. about, and 13 (8.44%) died from other causes indicate the over all survival is 79.22% Conclusions: Orthotopic neobladder reconstruction provides excellent continence rates, and both acceptable complication and mortality rates. Suitable patients undergoing radical cystectomy should be offered orthotopic neobladder reconstruction. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.7-13